The multi-site church revolution : being one church-- in many locations - Surratt, Geoff, 1962-; Ligon, Greg, 1962-; Bird, Warren (Grand Rapids, Mich. : Zondervan, 2006)
"Fueled by a desire to reach people for Christ, a revolution is underway. Churches are growing beyond the limitations of a single service in one building. Expanding the traditional model, they are embracing the concept of one church with more than one site: multiple congregations sharing a common vision, budget, leadership, and board. Drawing from the examples of churches nationwide, The Multi-Site Church Revolution shows what healthy multi-site churches look like and what motivates congregations to make the change. Discover how your church can: cast a vision for change; ensure a successful DNA transfer (vision and core values) to its new site; develop new leaders; fund new sites; adapt to structure and staffing change; use technology to support your worship services you'll identify the reasons churches succeed and how they overcome common snags. The Multi-Site Church Revolution offers guidance, insights, and specific action steps as well as appendixes with practical leadership resources and self-diagnostic tools." -- Publisher's description.
Part 1: The birth of the multi-site movement -- You say you want a revolution? Meet several highly successful multi-site churches -- A wide variety of models: Notice the broad range of models in this overview of the multi-site movement -- Part 2: How to become one church in many locations -- Would it work for you? Consider why your church should explore multi-site as a strategy -- On a mission from God : Discern God's call for your church and leadership -- Opportunity knocks : Don't expect "We've ways done it this way" to become your church motto -- Selling the dream : Learn how to use effective vision casting, helpful language, and strategic field trips -- Who's going to pay for this? Discover how to do multi-site in ways your church can afford -- Launching the mission : Evaluate these common factors in the successful launch of a second location -- Part 3: What makes multi-site work best -- Hitting the sweet spot : Make sure to define and replicate your unique DNA with help from these ideas -- Designing the right structure : Learn to grow at multiple locations by modifying the way you staff, structure, and communicate -- Building better leaders : Experience success by emphasizing the role of campus pastors, developing the next generation of leaders, and promoting from within -- Leveraging technology : Find the right balance of technology, whether you use in-person teaching or video -- Avoiding detours : Learn important lessons from churches that have taken wrong turns or hit roadblocks -- Part 4: Why extend further and reach more people? -- Secrets of ongoing replication : Don't let your dream stop short of developing an entire movement of replicating campuses -- Where do we go from here? Be part of turning the tide in a battle being lost by current approaches to doing church.
Includes bibliographical references (pages 211-214) and indexes.
Keywords: Multi-site churches; Church management